Melanoma of nasal cavity. Literature review and clinical case report - Krasovskaya, N. Y.; Meleshkina, I. V.; Kashirin, V. A. (Modern medical technology, 2020)
Primary malignant melanoma of the nose mucosa is a rare disease and seen in less than 0,5–0,7% among all melanomas, but has a worse prognosis because of its aggressiveness compared with that of the cutaneous form. Most of the nasal melanomas are not detected in early stage and survival statistics have not improved over the last years. The incisional biopsy is contraindicated, as this may increase metastatic spread. Cytology is definitely a simpler and safer method of getting a quick diagnosis. Most melanomas of nasal mucosa were found when infiltrating muscle, cartilage, or bone, that’s why craniofacial resection remains the «gold standard» for these tumors, but and endoscopic resection of sinonasal mucosal melanoma (at limited tumors) has comparable outcomes to open approaches. In report review the relevant medical literature (clinic, classification, histology, treatment and survival) and case observation of patient with primary nasal malignant melanoma.